Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/mrd.23467
|View full text |Cite
|
Sign up to set email alerts
|

The protein phosphatase with EF‐hand domain 1 is a calmodulin‐binding protein that interacts with proteins involved in sperm capacitation, binding to the zona pellucida, and motility

Abstract: Spermatozoa are highly specialized cells whose fertilizing and motility functions highly depend on intracellular Ca2+‐mediated events and protein posttranslational modifications like phosphorylation. Our group previously identified PPEF1, the Ser/Thr phosphatase with EF‐hand domain 1, among calmodulin‐affinity pulled down sperm proteins. As the mammalian ortholog of the Drosophila phosphatase rdgC that dephosphorylates rhodopsin, PPEF1 has been studied mostly in the retina. The presence and importance of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Further literature analysis of these ten phosphatases (PPM1B, STYXL1, PGP, EYA4, CDC14A, PPEF1, DUSP21, DUSP13, PP2D1, and HDHD1A) showed that (Fig. 1C ) three phosphatases, including PPM1B, PGP and EYA4, are essential to prevent embryonic lethality 33 35 ; deletion of Cdc14a causes spermatogenic defects 36 ; DUSP13 is involved in meiosis regulation; 37 PPEF1 is related to sperm fertilizing and motility 38 ; PP2D1 is dispensable for spermatogenesis 39 ; HDHD1A may be central in the epigenetic and genomic regulation of sex chromosome aneuploidies 40 . Only STYXL1 and DUSP21 have not been studied before in mouse, while STYXL1 is highly conserved from elegans to humans according to multiple sequence alignment analysis (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further literature analysis of these ten phosphatases (PPM1B, STYXL1, PGP, EYA4, CDC14A, PPEF1, DUSP21, DUSP13, PP2D1, and HDHD1A) showed that (Fig. 1C ) three phosphatases, including PPM1B, PGP and EYA4, are essential to prevent embryonic lethality 33 35 ; deletion of Cdc14a causes spermatogenic defects 36 ; DUSP13 is involved in meiosis regulation; 37 PPEF1 is related to sperm fertilizing and motility 38 ; PP2D1 is dispensable for spermatogenesis 39 ; HDHD1A may be central in the epigenetic and genomic regulation of sex chromosome aneuploidies 40 . Only STYXL1 and DUSP21 have not been studied before in mouse, while STYXL1 is highly conserved from elegans to humans according to multiple sequence alignment analysis (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%